2023
DOI: 10.1002/lno.12410
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton community response to episodic wet and dry aerosol deposition in the subtropical North Atlantic

Abstract: Atmospheric aerosol deposition into the low latitude oligotrophic ocean is an important source of new nutrients for primary production. However, the resultant phytoplankton responses to aerosol deposition events, both in magnitude and changes in community composition, are poorly constrained. Here, we investigated this with 19 d of field and satellite observations for a site in the subtropical North Atlantic. During the observation period, surface dissolved aluminum concentrations alongside satellite‐derived ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 73 publications
2
6
0
Order By: Relevance
“…Concentrations of dissolved Fe were analyzed following preconcentration on a SeaFAST device using inductively coupled plasma mass spectrometry (ICP‐MS; Element XR, Thermo Scientific), with quantification by isotope dilution (Rapp et al 2017). Certified values for GEOTRACES standards GSP and GSC matched well with our measured values (Yuan et al 2023).…”
Section: Methodssupporting
confidence: 89%
See 4 more Smart Citations
“…Concentrations of dissolved Fe were analyzed following preconcentration on a SeaFAST device using inductively coupled plasma mass spectrometry (ICP‐MS; Element XR, Thermo Scientific), with quantification by isotope dilution (Rapp et al 2017). Certified values for GEOTRACES standards GSP and GSC matched well with our measured values (Yuan et al 2023).…”
Section: Methodssupporting
confidence: 89%
“…In this event, atmospheric aerosols, typically characterized by an N : P ratio of > 500 (Baker et al 2010; Zamora et al 2013), were deposited into surface seawater. Yuan et al (2023) showed that this extra N supply was quickly exhausted to support a ~ 2‐fold increase in Chl a biomass (also see Table 1). Making the reasonable assumption that P supply from the rainfall event was minimal (Baker et al 2010; Zamora et al 2013), we hypothesize that this external N supply and the subsequent phytoplankton biomass enhancement depleted bioavailable P in seawater (including phosphate and bioavailable dissolved organic P).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations